Redescubramo-nos na sua experiência: O desafio que nos lança Ivar Oddone - Marianne Lacomblez; Ricardo Vasconcelos (Universidade do Porto, 2005)
Anchored in the works of Ivar Oddone, this paper tries to reconstruct a research path with particular utility for activating a new reflection on how to develop a work psychology centred on the workingman and on his experience. In an upfront and informal style, reflecting Oddone´s character and the "non-rituality" of the documents on which this paper is based, we will start at the first reflections and concepts through which we originally met Oddone: the rediscovery of workers´ experience and its importance for the transformation of work itself. From that, we will derive matters of method as well as Oddone´s proposals for experience construction and for the exploration of its transforming potential. In this regard the "instructions to a double" stand in a place of honour. The text will be developed around the concepts of "language", "system" and "interface", materialized in concrete situations on which Oddone´s team has been reflecting. Particular relevance will be given to his System of Concrete Information (SIC, in its original acronym), from which we will try to set some reflections and challenges elicited by Oddone´s works.